2020
DOI: 10.7717/peerj.8840
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a type 2 modified live porcine reproductive and respiratory syndrome vaccine against heterologous challenge of a lineage 3 highly virulent isolate in pigs

Abstract: Porcine reproductive and respiratory syndrome (PRRS) is one of the most common diseases in the global swine industry. PRRSV is characterized by rapid mutation rates and extensive genetic divergences. It is divided into two genotypes, which are composed of several distinct sub-lineages. The purpose of the present study was to evaluate the cross-protective efficacy of Fostera PRRS MLV, an attenuated lineage 8 strain, against the heterologous challenge of a lineage 3 isolate. Eighteen pigs were randomly divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Although the reduction of PRRSV viremia is a critical parameter for the evaluation of PRRSV vaccines, the mechanisms of the viral clearance are still poorly understood. PRRSV viremia is often resolved even before neutralizing antibodies (NA) are detected in infected pigs [ 18 , 20 , 21 , 22 ] and vaccinated pigs [ 23 , 24 , 25 , 26 ]. Despite the low NA levels in response to PRRSV vaccination [ 23 , 24 , 27 ], pigs that received a MLV vaccine followed by a PRRSV challenge still efficiently cleared PRRSV in the blood.…”
Section: Respiratory Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the reduction of PRRSV viremia is a critical parameter for the evaluation of PRRSV vaccines, the mechanisms of the viral clearance are still poorly understood. PRRSV viremia is often resolved even before neutralizing antibodies (NA) are detected in infected pigs [ 18 , 20 , 21 , 22 ] and vaccinated pigs [ 23 , 24 , 25 , 26 ]. Despite the low NA levels in response to PRRSV vaccination [ 23 , 24 , 27 ], pigs that received a MLV vaccine followed by a PRRSV challenge still efficiently cleared PRRSV in the blood.…”
Section: Respiratory Diseasesmentioning
confidence: 99%
“…Measurement of IFN-γ secreting cells (IFN-γ-SC) is a frequently used tool for evaluating the recall IFN-γ responses after vaccination or infection. Numerous vaccinate-challenge studies found a significant negative correlation between the IFN-γ response and blood viral load, indicating induction of IFN-γ responses by MLV vaccine may result in the reduction of viremia [ 23 , 25 , 26 , 32 , 33 , 34 , 35 ]. Cell-mediated immune response is therefore an important component in the clearance of PRRSV viremia.…”
Section: Respiratory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, vaccine strains were compared only to sequences within the same lineage to illustrate its potential impact on lineage diversity. However, the decision of which vaccine will be used is not necessarily lineage-based, as PRRSV lineage classification has only recently gained traction for routine diagnosis and vaccines show variable heterologous protection, particularly in reducing clinical signs and lesions against unrelated isolates [30][31][32]. We decided to use an arbitrary <5% nucleotide identity to a vaccine-strain as cutoff to define vaccine-like sequences instead of their relative distances to the parental or vaccine strains, the latter of which could be interpreted as a metric of the overall divergence of the virus.…”
Section: Plos Onementioning
confidence: 99%
“…The limited efficacy of cross-protection from commercial MLV vaccines against NADC30-like viruses might be an important reason that these viruses widely spread and became the predominant PRRSV strains in China [ 117 , 119 , 120 , 121 ]. Furthermore, the Fostera ® PRRS MLV from lineage 8 of PRRSV-2 is also confirmed to confer partial cross-protection against the heterologous challenge of a virulent PRRSV strain from lineage 3 [ 122 ]. To improve the heterologous protection efficacy, some immune boosters or regulators, such as quercetin and Quil A, which are regarded to be able to upgrade the mRNA expression of interferon and many other helpful cytokines, were orally taken or injected together with PRRS MLV.…”
Section: Protection Efficacy Of Prrs MLVmentioning
confidence: 99%